“Elaboración de un mapa de calidad del café (coffea arábica) situadas en ocho zonas de la provincia de Lamas” - Aquino Yaringaño, Sonia Celia (2004)
The necessity of "to Elaborate a map of quality of coffee (Arabic Coffea) located in eight coffee areas of the County of you Lick", locates among the 800 to 1570 m.s.n.m. lt is of supreme importance to market long term coffee of high quality, to more prices and of grateful quality. This investigation looks for to standardize the quality of coffee in two levels of altitudes (800 to 1200 m.s.n.m. and 1200 to 1570 m.s.n.m.) and eight committees, in cosecha y beneficio (traditional and select), according to the Norma Peruvian Technique 209.027 -2001. The data to carry out the investigation work have been obtained of 144 farmers contained in eight committees belonging to the coffee Agrarian Cooperative "I Pray Green" Ltda. The yields of the committees in crop and traditional benefit were Nueva Chota with 76 yield% and 35 defects; High Shamboyacu 75 yield% with 30 defects respectively, and in crop and select benefit the yields improved in the different committees, less in the town of Pamashto and Alan García. The end punctuation for analysis organoléptico in heights understood among 800 to 1570 m.s.n.m. it doesn't show significant statistical differences (ANVA ANO DUNCAN), there is certain tendency of being presented better in superior heights at 1200. The select system was the best. In the end punctuation of the analysis organoléptico in eight committees show highly significant differences in ANVA and DUNCAN. The committees that occupy the first place are: Somos Libres, Nueva Chota, Mirador Roque and Shamboyacu, the second place: Canaan and Chirapa and the third place: Pamashto and Alan Garcla. In the end punctuation of the analysis organoléptico in technology of traditional and select cosecha y beneficio for committees is highly significant statistical differences in ANVA and DUNCAN. The select system was the best. In the end punctuation of the analysis organoléptico in the interaction committees for crop technology is not difference statistic however in ANVA in DUNCAN differences they are observed. The best combinations of committees for select technology are Somos Libres, Nueva Chota, Mirador Roque and Shamboyacu; it is necessary to clarify that the committees of Nueva Chota and Shamboyacu also present a good combination with the traditional system of cosecha y beneficio.